The Differential Axonal Degradation of Ret Accounts for Cell-Type-Specific Function of Glial Cell Line-Derived Neurotrophic Factor as a Retrograde Survival Factor - Tsui, Cynthia C. (Society for Neuroscience, 2010)
Glial cell line-derived neurotrophic factor (GDNF) is a neuronal growth factor critical for the development and maintenance of central and peripheral neurons. GDNF is expressed in targets of innervation and provides support to several populations of large, projection neurons. To determine whether GDNF promotes retrograde survival over long axonal distances to cell bodies, we used a compartmentalized culture system. GDNF supported only modest and transient survival of postnatal sympathetic neurons when applied to their distal axons, in contrast to dorsal root ganglion (DRG) sensory neurons in which GDNF promoted survival equally well from either distal axons or cell bodies. Ret, the receptor tyrosine kinase for GDNF, underwent rapid proteasomal degradation in the axons of sympathetic neurons. Interestingly, the level of activated Ret in DRG neurons was sustained in the axons and also appeared in the cell bodies, suggesting that Ret was not degraded in sensory axons and was retrogradely transported. Pharmacologic inhibition of proteasomes only in the distal axons of sympathetic neurons caused an accumulation of activated Ret in both the axons and cell bodies during GDNF stimulation. Furthermore, exposure of the distal axons of sympathetic neurons to both GDNF and proteasome inhibitors, but neither one alone, promoted robust survival, identical to GDNF applied directly to the cell bodies. This differential responsiveness of sympathetic and sensory neurons to target-derived GDNF was attributable to the differential expression and degradation of the Ret9 and Ret51 isoforms. Therefore, the local degradation of Ret in axons dictates whether GDNF family ligands act as retrograde survival factors.